An assessment of the constitution of the Evangelical Lutheran Church in southern Africa within the Bill of Rights as enshrined in the South African Constitution Act 108/1996 - Hofmeyr, J.W. (Johannes Wynand), 1947- (University of Pretoria, 2013)
Dissertation (MA(Theology) Church History)--University of Pretoria, 2008.